Introduction to “On Whose Terms?” - Ballentine, Debra Scoggins (Method & theory in the study of religion, 2025)
This special issue, “On Whose Terms …?” addresses some challenges of working within standard comparative methodologies from the joint perspectives of Daoist Studies and the Study of Judaism. We offer our explorations of various theories, methodologies, case studies, and the history of the field of Religious Studies, with special focus on Daoist Studies and the Study of Judaism. Collectively, we aim to provide models for circumventing the limits that scholars face with the categories that define “religion.”